Salmonella employs multiple mechanisms to subvert the TLR‐inducible zinc‐mediated antimicrobial response of human macrophages. Issue 5 (2nd February 2016) - Kapetanovic, Ronan; Bokil, Nilesh J.; Achard, Maud E. S.; Ong, Cheryl‐lynn Y.; Peters, Kate M.; Stocks, Claudia J.; Phan, Minh‐Duy; Monteleone, Mercedes; Schroder, Kate; Irvine, Katharine M.; Saunders, Bernadette M.; Walker, Mark J.; et al.
Abstract : We aimed to characterize antimicrobial zinc trafficking within macrophages and to determine whether the professional intramacrophage pathogen Salmonella enterica serovar Typhimurium ( S. Typhimurium) subverts this pathway. Using both Escherichia coli and S. Typhimurium, we show that TLR signaling promotes the accumulation of vesicular zinc within primary human macrophages. Vesicular zinc is delivered to E. coli to promote microbial clearance, whereas S. Typhimurium evades this response via Salmonella pathogenicity island (SPI)‐1. Even in the absence of SPI‐1 and the zinc exporter ZntA, S. Typhimurium resists the innate immune zinc stress response, implying the existence of additional host subversion mechanisms. We also demonstrate the combinatorial antimicrobial effects of zinc and copper, a pathway that S. Typhimurium again evades. Our use of complementary tools and approaches, including confocal microscopy, direct assessment of intramacrophage bacterial zinc stress responses, specific E. coli and S. Typhimurium mutants, and inductively coupled plasma mass spectroscopy, has enabled carefully controlled characterization of this novel innate immune antimicrobial pathway. In summary, our study provides new insights at the cellular level into the well‐documented effects of zinc in promoting host defense against infectious disease, as well as the complex host subversion strategies employed by S. Typhimurium to combat this pathway.—Kapetanovic, R., Bokil, N. J., Achard, M. E. S., Ong, C.‐L. Y., Peters, K. M., Stocks, C. J., Phan, M.‐D., Monteleone, M., Schroder, K., Irvine, K. M., Saunders, B. M., Walker, M. J., Stacey, K. J., McEwan, A. G., Schembri, M. A., Sweet, M. J. Salmonella employs multiple mechanisms to subvert the TLR‐inducible zinc‐mediated antimicrobial response of human macrophages. FASEB J. 30, 1901–1912 (2016). www.fasebj.org